THE EFFECT OF MAKE A MATCH AND SCRAMBLE LEARNING MODEL ON LEARNING OUTCOMES - Fenny Mustika Piliang (Sean Institute, 2021)
This research aims to determine the effect of the make a match and scramble learning model on student learning outcomes at MTs Pembina Maligas Bayu Simalungun, North Sumatra. The experimental design used a pre-test post-test which was conducted on 35 students for experiment I and 35 students for experiment II. The student sample was taken by a cluster random sampling. The data collected using multiple choice tests. Analysis of the data findings using the t test. The results of the research reveal that the make a match and scramble learning models have a good influence on improving student learning outcomes. Based on the analysis of research data, the facts found are the increase in the value of student learning outcomes with the make a match learning model is greater than the Scramble learning model. This proves that the Make A Match learning model has a good effect on the learning outcomes of class VIII MTs Pembina Maligas Bayu. This research recommends that the make a match and scramble learning models can be used to improve student learning outcomes, especially the excretory system material.